2007
DOI: 10.1111/j.1365-2966.2007.12143.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the search for binaries among Am stars – VIII. New spectroscopic orbits of eight systems and statistical study of a sample of 91 Am stars

Abstract: International audienceThis paper is the last of a series devoted to the study of Am stars, with the monitoring of radial velocities of a sample of 91 objects during more than 20 yr. The purpose was to determine which stars were members of spectroscopic binaries (SBs) and study in detail those systems in order to obtain observational constraints on the origin of the Am phenomenon. In the first part, we present the results of a detailed study of eight Am stars (HD 32893, 60489, 109762, 111057, 113697, 204918, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 51 publications
9
57
0
Order By: Relevance
“…The period distribution is, however, slightly different, with a pronounced peak at shorter periods due to the inclusion of close binaries. The v sin i distributions of both Abt & Levy (1985) and Carquillat & Prieur (2007) are skewed toward lower values than the Renson & Manfroid (2009) sample. These RV studies have preferentially avoided stars with high rotation, which accounts for the excess of short period systems found in the WASP sample.…”
Section: Expected Period Distribution Of Am Binariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The period distribution is, however, slightly different, with a pronounced peak at shorter periods due to the inclusion of close binaries. The v sin i distributions of both Abt & Levy (1985) and Carquillat & Prieur (2007) are skewed toward lower values than the Renson & Manfroid (2009) sample. These RV studies have preferentially avoided stars with high rotation, which accounts for the excess of short period systems found in the WASP sample.…”
Section: Expected Period Distribution Of Am Binariesmentioning
confidence: 99%
“…Comprehensive spectroscopic radial velocity studies of carefully selected Am stars, have found a binary fraction of nearer 60−70% (Abt & Levy 1985;Carquillat & Prieur 2007). The period distribution shows that the majority of systems have periods < ∼ 50 days, consistent with the slow rotation being due to tidal synchronisation or pseudo-synchronisation (Budaj 1996(Budaj , 1997.…”
Section: To Conclude Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…Abt & Levy 1985;Carquillat & Prieur 2007;Debernardi 2002). According to, e.g., Budaj (1997), systems with 1 < P < 35 days owe their slow rotation to tidal effects, either through synchronisation (for periods up to 12 days) or to pseudo-synchronisation (for eccentric systems).…”
Section: Introductionmentioning
confidence: 99%
“…Triggered by the study of Carquillat & Prieur (2007, MNRAS, 380, 1064 of Am binaries, I reanalyse their sample of 60 orbits to derive the mass ratio distribution (MRD), assuming as they did a priori functional forms, i.e. a power law or a Gaussian.…”
Section: Introductionmentioning
confidence: 99%